MACHINE LEARNING FOR HUMAN RECOGNITION - Surikovs, Deņiss; Mežārs, Andrejs; Bleive, Ritvars; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2023)
The aim of this work is to develop a neural network that will be able to recognize human presence. To achieve this goal, authors applied neural network architecture YOLOv5 and the open dataset COCO. The experiment was repeated three times. The study yielded a good result - the neural network was able to detect humans in images with a good precision.